Bay’āh Perempuan dalam Al-Qur’an dan Sirâh: Interpretasi Teks, Konteks, dan Relevansi Modern - Qurroh A’yuniyah; Ulifatur Rizqoh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study presents an in-depth analysis of the concept of women's bay'ah as articulated in QS. Al-Mumtahanah verse 12, emphasizing its rich normative values, historical significance, and relevance within contemporary discourses on gender equality. Employing thematic interpretation and hermeneutic approaches, the study comprehensively examines the Qur’anic text, the Prophetic biography, as well as both classical and modern exegeses to reveal the fundamental values inherent in the practice of bay'ah. The findings indicate that women's bay'ah not only reflects an acknowledgment of the significant contributions of women in the establishment of early Islamic society but also reaffirms essential principles such as monotheism, morality, and adherence to leadership grounded in justice and universal benevolence. Utilizing a qualitative methodology based on library research, this systematic analysis integrates historical data with modern perspectives to yield deep insights into the dynamic interplay between sacred texts and contemporary social contexts. The study is expected to enrich academic discourse, serve as a strategic reference for practitioners and policymakers in formulating inclusive societal development strategies, and foster a critical dialogue between tradition and innovation in Islamic studies. Moreover, the comparative analysis of various interpretative approaches in the history of Islamic thought successfully illustrates the evolution of gender understanding, contributing significantly to the development of a more progressive and contextually relevant Islamic paradigm.